2017
DOI: 10.1515/jccm-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

The First Manifestation of a Left Atrial Myxoma as a Consequence of Multiple Left Coronary Artery Embolisms

Abstract: A case of multiple embolisms in the left coronary artery as a rare first manifestation of left atrial myxoma is reported. A patient with embolic myocardial infarction and congestive heart failure was treated by percutaneous aspirations and balloon dilatations. Transesophageal echocardiography disclosed a villous myxoma with high embolic potential. Surgical resection of the tumour, suturing of a patent foramen ovale suture and an annuloplasty of the dilated tricuspid annulus was performed the third day after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…10 However, the real incidence of CA embolisms may be higher, due to a potential incomplete detection of all patients suffering from MI or sudden cardiac death. 11 In this context, abnormal, but non-specific, rhythm disturbances like atrial flutter/fibrillation, bundle branch block (right or left) are identified in 20%-40% of myxoma patients, while tachyarrhythmias are observed in about 24%-25.7% of the cases. 2 Gold standard management for symptomatic patients is immediate surgical en bloc tumor removal with clear margins, when technically achievable.…”
Section: Case Reportmentioning
confidence: 99%
“…10 However, the real incidence of CA embolisms may be higher, due to a potential incomplete detection of all patients suffering from MI or sudden cardiac death. 11 In this context, abnormal, but non-specific, rhythm disturbances like atrial flutter/fibrillation, bundle branch block (right or left) are identified in 20%-40% of myxoma patients, while tachyarrhythmias are observed in about 24%-25.7% of the cases. 2 Gold standard management for symptomatic patients is immediate surgical en bloc tumor removal with clear margins, when technically achievable.…”
Section: Case Reportmentioning
confidence: 99%
“…Typically known for causing noticeable symptoms, myxomas rarely manifest without any apparent signs. 6 We present a rare and interesting case of a large asymptomatic left atrial myxoma incidentally discovered during breast cancer restaging studies.…”
Section: Introductionmentioning
confidence: 97%
“…Los tumores cardiacos son raros con una incidencia que varía de 0.002% a 0.02%. La mayoría es benigno (Novak M, et al;, con múltiples formas de presentación por lo que a pesar de su rareza es importante tenerlos como diagnóstico diferencial ante un paciente que presente sintomatología cardiaca sin factores de riesgo cardiovasculares.…”
Section: Introductionunclassified